Lost and found : young fathers in the age of unwed parenthood - Florsheim, Paul; Moore, David (Professor of psychology) (New York, NY : Oxford University Press, 2019)
'Lost and Found is about how young men learn to be fathers and how we, as a society, can facilitate that learning and help stabilize families. Paul Florsheim and David Moore introduce a diverse group of young men whose stories represent different trajectories of young fatherhood. The stories featured in this book begin soon after these young men find out their partners are pregnant and move in different, and often unexpected, directions. Some young men--even those with significant problems--grow into parenthood and speak eloquently about connecting with their children. A few speak with disarming candor about becoming disconnected and lost. In six parts, Florsheim and Moore weave the individual stories of these young men into the larger story of fatherhood in 21st century America. While there is little doubt that America has a'fatherhood problem' characterized by high rates of father absence, Florsheim and Moore focus on understanding new family types and looking for ways to ensure their stability. They draw from the work of evolutionary biologists, social historians, developmental psychologists, and marital therapists to make sense of what goes wrong between young fathers and their families, seeking information about how some young men learn--despite the odds against them--to become'good enough' fathers. In the last section, Lost and Found builds a case for providing young men with more concrete institutional support and presents a plan for integrating expectant fathers into prenatal care, helping them become fathers, just as we currently help their partners become mothers. young fathers; adolescent parents; parenthood; co-parenting; father absence; family stability; father development; developmental psychology; prenatal care; co-parenting counselling'--
Keywords: Teenage fathers -- United States; Unmarried fathers -- United States; Fatherhood -- United States; Family services -- United States